Psychology and Performance: Revisiting Rhoads’ “Performance Criticism : An Emerging Methodology in Second Temple Studies” - Iverson, Kelly R. ca. 20./21. Jh. (Biblical theology bulletin, 2025)
In 2006, David Rhoads published a two-part BTB article introducing the discipline of performance criticism. Almost twenty years later, the essays have become foundational to the discussion of biblical performance. The following study revisits several of the arguments advanced by Rhoads through the perspective of the psychological sciences. The analysis devotes particular attention to understanding the cognitive processes and experiential impacts associated with narrative engagement to appreciate how the modalities of reading and performance both intersect and diverge. The study concludes that, although Rhoads may have overstated his case in certain instances, the psychological literature broadly affirms his conclusions, enriching and extending the discussion through a methodological perspective that has been underutilized among performance critics.